A review of ceramic/bio-based hybrid reinforced aluminium matrix composites. Issue 1 (1st January 2020) - Peter P., Ikubanni; M., Oki; Adekunle A., Adeleke
Abstract: The quest for light and durable materials which can withstand harsh conditions of modern advanced applications in many fields such as aviation, automobile, sport, and so on, has been scientifically sought for. Studies in the last few decades have found aluminium metal composites (AMCs) reinforced with bio-based fibres of diverse origins as a suitable advanced material because of improved physical and mechanical properties that are obtainable. Such reinforcements may be single (usage of one reinforcement) or hybridized (more than one reinforcement) with synthesized particulate materials; however, they impart better physico-mechanical and wear behavior on the aluminium alloy matrix. Thus, this review examines some of these composites produced by stir-casting procedures and their properties currently trending in materials research circles. It has been established that by varying parameters such as stirring speed/time and reinforcement types and composition, the use of stir casting process is a viable method to produce AMCs with good physical properties, mechanical properties, and wear behavior. AMCs are eminently useful in the production of parts for the automotive, aerospace and aviation industries.